Mrs. Jekyll : a novel - Glass, Emma (Union Square & Co, 2026)
"A brilliant, feminist retelling of Robert Louis Stevenson's evergreen classic, The Strange Case of Dr. Jekyll & Mr. Hyde, in which a woman gives in to the murderous and sensual force that awakens within her as she battles the ravages of breast cancer"-- Provided by publisher.